Silicon, by promoting a homeostatic balance of C:N:P and nutrient use efficiency, attenuates K deficiency, favoring sustainable bean cultivation - Costa, Milton G. [UNESP]; Prado, Renato de M. [UNESP]; Santos Sarah, Marcilene M. [UNESP]; Souza Júnior, Jonas P. [UNESP]; de Souza, Antonia Erica S. [UNESP] (My University, 2023)
Background: In many regions of the world, K is being depleted from soils due to agricultural intensification a lack of accessibility, and the high cost of K. Thus, there is an urgent need for a sustainable strategy for crops in this environment. Si is an option for mitigating stress due to nutritional deficiency. However, the underlying effects of Si in mitigating K deficiency C:N:P homeostasis still remains unknown for bean plants. This is a species of great worldwide importance. Thus, this study aims to evaluate whether i) K deficiency modifies the homeostatic balance of C, N and P, and, if so, ii) Si supply can reduce damage caused to nutritional stoichiometry, nutrient use efficiency, and production of dry mass in bean plants. Results: K deficiency caused a reduction in the stoichiometric ratios C:N, C:P, and P:Si in shoots and C:N, C:P, C:Si, N:Si, and P:Si in roots, resulting in a decrease in K content and use efficiency and reducing biomass production. The application of Si in K-deficient plants modified the ratios C:N, C:Si, N:P, N:Si, and P:Si in shoots and C:N, C:P, C:Si, N:Si, N:P, and P:Si in roots, increasing the K content and efficiency, reducing the loss of biomass. In bean plants with K sufficiency, Si also changed the stoichiometric ratios C:N, C:P, C:Si, N:P, N:Si, and P:Si in shoots and C:N, C:Si, N:Si, and P:Si in roots, increasing K content only in roots and the use efficiency of C and P in shoots and C, N, and P in roots, increasing the biomass production only in roots. Conclusion: K deficiency causes damage to the C:N:P homeostatic balance, reducing the efficiency of nutrient use and biomass production. However, Si is a viable alternative to attenuate these nutritional damages, favoring bean growth. The future perspective is that the use of Si in agriculture in underdeveloped economies with restrictions on the use of K will constitute a sustainable strategy to increase food security.
Keywords: Beneficial element; K sufficiency; Nutritional stoichiometric ratios; Nutritional stress; Phaseolus vulgaris L